Blood metabolomics analysis identifies differential serum metabolites in elite and sub-elite swimmers - Cai, M.; Wu, C.; Jing, C.; Shen, X.; He, M.; Wang, L.; Guo, Q.; Yan, Y.; Yan, X.; Yang, R. (Frontiers in Physiology, 2022)
Objective: Metabolites in body fluids, such as lactate, glucose, and creatinine, have been measured by conventional methods to evaluate physical function and performance or athletic status. The objectives of the current study were to explore the novel metabolite biomarkers in professional swimmers with different competition levels using nuclear magnetic resonance (NMR) metabolomics, and try to establish a model to identify the athletic status or predict the competitive potential.